PERLINDUNGAN HUKUM BAGI PEMEGANG HAK CIPTA SINEMATOGRAFI TERHADAP PEMBAJAKAN FILM YANG DISEBARKAN DI APLIKASI TIKTOK - Achmad Rafi Al Khalish, (2023)
Many Indonesians are social media users, amounting to 191.4 million in January 2022, based on research from DataReportal. One of the famous social media is TikTok. TikTok is a social media to create and distribute various short videos in a vertical format, which is used only to swipe the screen down or up. However, there is a violation on TikTok, namely the piracy of a film that is a work of cinematography, which is spread through this social media. There is movie piracy on TikTok, namely the hijacking of Habibie & Ainun 3 which was carried out by @brdn97 account. The purpose of the study is to analyze the legal protection for cinematographic copyright holders against piracy of films spread on the TikTok application and analyze TikTok's responsibility for cinematographic copyright infringement. The research method used in this study is the normative juridical method using a statutory approach. This research found that the protection for the copyright holders of the Habibie & Ainun 3 film, namely preventive and repressive, is contained in Law Number 28 of 2014 concerning Copyright. TikTok has been registered as a Private Scope Electronic System Operator by the Ministry of Communication and Informatics (Kominfo), therefore TikTok is bound by Kominfo regulations. TikTok must cut off access, namely the removal of the hijacking content of the film Habibie & Ainun 3 on TikTok.